Investigation on Structural and Optical Properties of ZnO Film Prepared by Simple Wet Chemical Method - Sholehah, Amalia; Mulyadi, Rendi; Haryono, Didied; Muttakin, Imamul; Rusbana, Tb Bahtiar; Mardiyanto, Mardiyanto (IPTEK Journal of Proceedings Series, 2018)
ZnO thin layer has a broad potential application in electronic and optoelectronic devices. In this study, vertically align ZnO layers were deposited on ITO glass using wet chemistry method. The seed layers were prepared using electrodeposition technique at 3Â°C. The growing process was carried out using chemical bath deposition at 90Â°C. To improve the structural properties, two different hydrothermal treatment variations were applied separately. From the experiment, it is shown that the hydrothermal process using N2 gas has given better results, compared to the conventional treatment.